1987
DOI: 10.1038/325249a0
|View full text |Cite
|
Sign up to set email alerts
|

Left hemisphere advantage in the mouse brain for recognizing ultrasonic communication calls

Abstract: In humans, sound perceived as speech is processed preferentially by the right ear and the left hemisphere of the brain. Among animals, such an advantage of one hemisphere (lateralization) in processing communication sound from other members of the species has so far been demonstrated only in macaque monkeys. I report here that in the house mouse, which has a very much less elaborate forebrain than man or macaque monkey, the ultrasonic calls that are emitted by young mice to evoke maternal caring behavior are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
147
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(167 citation statements)
references
References 9 publications
18
147
0
2
Order By: Relevance
“…Since projections to the midbrain arise primarily from the contralateral auditory periphery, the results obtained here support the hypothesis that right-ear/left-hemispheric superiority for processing communication sounds in frogs is to a significant extent due to structural asymmetries in the way the auditory system processes information. This finding is also in agreement with earlier studies on REA in amniote vertebrates holding a left-hemisphere priority for processing conspecific/neighbor vocalizations [1,[16][17][18][19]24,[52][53][54][55][56][57]. Furthermore, the REA in music frogs has been demonstrated, at least in part, in a preliminary behavioral study using a head orienting task in which the subjects preferentially turned their bodies toward the right while listening to HSA playbacks, but did not show a turning preference in silence (unpublished data).…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 91%
See 1 more Smart Citation
“…Since projections to the midbrain arise primarily from the contralateral auditory periphery, the results obtained here support the hypothesis that right-ear/left-hemispheric superiority for processing communication sounds in frogs is to a significant extent due to structural asymmetries in the way the auditory system processes information. This finding is also in agreement with earlier studies on REA in amniote vertebrates holding a left-hemisphere priority for processing conspecific/neighbor vocalizations [1,[16][17][18][19]24,[52][53][54][55][56][57]. Furthermore, the REA in music frogs has been demonstrated, at least in part, in a preliminary behavioral study using a head orienting task in which the subjects preferentially turned their bodies toward the right while listening to HSA playbacks, but did not show a turning preference in silence (unpublished data).…”
Section: Rea As a Mechanism For Processing Acoustic Stimulisupporting
confidence: 91%
“…For humans, speech sounds are mainly processed in the left auditory cortex while music sounds are processed in the right [58]. For non-human animals, left-hemispheric dominance for conspecific communication sounds has been reported in non-human primates [19,[53][54][55]59], other mammals [16,17,24,56,57], birds [60,61] and frogs [10]. Interestingly, communication asymmetry has been reported in bats at the level of single cortical neurons, with left-hemispheric neuronal advantage for processing social calls and right-hemispheric neuronal advantage in processing navigational signals [24].…”
Section: Rea As a Mechanism For Processing Acoustic Stimulimentioning
confidence: 99%
“…Our data, together with others on categorical perception (33,34) and left-hemisphere dominance of communication call perception in mice (35), point to the same mechanisms for the analysis and perception of communication sounds in mice and humans, with the consequence that the handling of speech sounds in the mammalian auditory system up to the perceptual level follows evolutionary old rules.…”
Section: Ranking Of Call Modelssupporting
confidence: 80%
“…Ehret and Haack [24] found that synthesized tones of a limited range of durations and major frequency components above 40 kHz elicited responses as strong as the natural ultrasonic calls of mouse pups. The neural circuitry underlying this response appears to be lateralized to the left hemisphere [23].…”
Section: Crying and Parental Behaviormentioning
confidence: 97%